Sand inundation on rocky shores : its effects on species richness and the structure of species assemblages - Dower, Katherine Mary (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1990)
Although sand deposits are present on many intertidal rocky shores, their effects on species richness, zonation and trophic structure have often been overlooked. This study is the first to recognise sand as an important abiotic factor on South African rocky shores. Rocky shores in the eastern Cape Province of South Africa are subject to extensive sand inundation and are composed of two hard substrata of differing topographies. Four sites on one substratum and six on the other were sampled quantitatively using quadrats. The biota were identified, counted and/ or weighed to provide a matrix of species biomass and numbers in separate zones. This matrix was then analysed using ordination and classification. A total of 321 species were identified which is more than local rocky or sandy shores. While the intermediate disturbance hypothesis would predict high species richness on these shores, it does not fully explain this richness nor the distribution of species assemblages. Habitat heterogeneity, including the dynamics of sand deposits, is strongly influenced by substratum topography and is the most important factor generating species richness. Abrasion by sand (sand scour) causes local reductions in richness but the presence of semi-permanent sand deposits allows habitation by psammophilic and sand-dependent species. As a result the biota of a sand inundated rocky shore includes both a full rocky shore and a large sandy beach component. Substratum topography controls patterns of sand deposition and retention and community analysis showed that samples were clustered primarily according to species richness and secondarily according to substratum type. Ordination of species identified an arc of species assemblages of decreasing levels of sand tolerance. These corresponded to sample groupings so that th assemblages found in various habitats were characterised by particular levels of sand tolerance. The presence of sand has a negative effect on the biomass of primary producers and filter feeders but a positive effect on the biomass of deposit feeders. Because sand is retained to different degrees in different zones, trophic structure varies between zones and to a lesser extent, between rock types. In general, however, the trophic structure of sand inundated rocky shores is similar to that of non-inundated shores.
Keywords: Intertidal ecology; Tide pool ecology